Liver resection and ablation for squamous cell carcinoma liver metastases. Issue 4 (24th August 2021) - Engstrand, J; Abreu de Carvalho, L F; Aghayan, D; Balakrishnan, A; Belli, A; Björnsson, B; Dasari, B V M; Detry, O; Di Martino, M; Edwin, B; Erdmann, J; Fristedt, R; et al.
Abstract: Background: Limited evidence exists to guide the management of patients with liver metastases from squamous cell carcinoma (SCC). The aim of this retrospective multicentre cohort study was to describe patterns of disease recurrence after liver resection/ablation for SCC liver metastases and factors associated with recurrence-free survival (RFS) and overall survival (OS). Method: Members of the European–African Hepato-Pancreato-Biliary Association were invited to include all consecutive patients undergoing liver resection/ablation for SCC liver metastases between 2002 and 2019. Patient, tumour and perioperative characteristics were analysed with regard to RFS and OS. Results: Among the 102 patients included from 24 European centres, 56 patients had anal cancer, and 46 patients had SCC from other origin. RFS in patients with anal cancer and non-anal cancer was 16 and 9 months, respectively ( P = 0.134). A positive resection margin significantly influenced RFS for both anal cancer and non-anal cancer liver metastases (hazard ratio 6.82, 95 per cent c.i. 2.40 to 19.35, for the entire cohort). Median survival duration and 5-year OS rate among patients with anal cancer and non-anal cancer were 50 months and 45 per cent and 21 months and 25 per cent, respectively. For the entire cohort, only non-radical resection was associated with worse overall survival (hazard ratio 3.21, 95 per cent c.i. 1.24 to 8.30). Conclusion: Liver resection/ablation of liver metastases from SCC can result in long-term survival. Survival was superior in treated patients with liver metastases from anal versus non-anal cancer. A negative resection margin is paramount for acceptable outcome. Abstract : Limited evidence exists to guide the management of patients with liver metastases from squamous cell carcinoma (SCC). The present study shows that hepatic resection/ablation of liver metastases from SCC can result in long-term survival.